What the Cardiologist Needs to Consider in the Management of Oncologic Patients with STEMI-Like Syndrome: A Case Report and Literature Review - Aneta Aleksova; Giulia Gagno; Alessandro Pierri; Carla Todaro; Alessandra Lucia Fluca; Valentina Orlando; Alessandra Guglielmi; Antonio Paolo Beltrami; Gianfranco Sinagra (MDPI AG, 2021)
In pre-hospital care, an accurate and quick diagnosis of ST-segment elevation myocardial infarction (STEMI) is imperative to promptly kick-off the STEMI network with a direct transfer to the cardiac catheterization laboratory (cath lab) in order to reduce myocardial infarction size and mortality. Aa atherosclerotic plaque rupture is the main mechanism responsible for STEMI. However, in a small percentage of patients, emergency coronarography does not reveal any significant coronary stenosis. The fluoropyrimidine agents such as 5-Fluorouracil (5-FU) and capecitabine, widely used to treat gastrointestinal, breast, head and neck cancers, either as a single agent or in combination with other chemotherapies, can cause potentially lethal cardiac side effects. Here, we present the case of a patient with 5-FU cardiotoxicity resulting in an acute coronary syndrome (ACS) with recurrent episodes of chest pain and ST-segment elevation.. Our case report highlights the importance of widening the knowledge among cardiologists of the side effects of chemotherapeutic drugs, especially considering the rising number of cancer patients around the world and that fluoropyrimidines are the main treatment for many types of cancer, both in adjuvant and advanced settings.